Perencanaan Lokasi Pabrik, Penetapan Kapasitas Produksi Dan Jumlah Mesin Yang Dibutuhkan Untuk Produksi Roda Gigi - Darma Aviva; Hidayat Hidayat; Abdul Halik (MEDIA PERSPEKTIF : Journal of Technology, 2020)
This research was conducted to plan the best location as a place for the establishment of factories that produce gears to meet the demand for gears in the East Kalimantan area. After the best location is obtained, determine the most optimal production capacity, taking into account all existing limitations including estimation of damaged products later in the production process. And finally, determine the number and type of machines needed to produce these gears. The analytical tool in this research is the Brown Gibson Method to determine the best factory location, quantitative and qualitative analysis so that the results obtained are closer to reality. The results obtained are for the best location for the establishment of a gear factory in Loa Buah Samarinda. Obtained the results of three types of machinery needed to produce gears are 5 units of lathe as the first stage process, the milling machine as the second stage process with a total of 11 units, and finally processed in a drill machine with 7 units of drilling machines needed . The production capacity is 442 products resulting from the first stage process with 13 products damaged, then 429 products are produced from the second stage process with 20 products damaged, and as many as 409 products produced from the last process in the form of gears with 9 broken gear products.